2005
DOI: 10.1590/s1677-55382005000400007
|View full text |Cite
|
Sign up to set email alerts
|

Testicular histopathological diagnosis as a predictive factor for retrieving spermatozoa for ICSI in non-obstructive azoospermic patients

Abstract: Objective: Histological testicular pattern has a predictive role in the possibility of finding spermatozoa for ICSI in cases of non-obstructive azoospermia because some individuals could show residual spermatogenic sites in the testis. The aim of this study was to evaluate the sperm retrieval rate in each of the histopathological groups (hypospermatogenesis-Hypo, spermatogenic maturation arrest-MA, Sertoli cell only-SCO and testicular hyalinization) in patients assisted in our clinic.Materials and Methods: Ret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…As mentioned previously, although diagnostic biopsy has significant predictive value, the chance that sperm cannot be retrieved on the day of oocyte retrieval is 25% -30% [Glina et al 2005]. Some have suggested that the cryopreservation of sperm from TESE before treatment should be implemented to prevent this situation [Wu et al 2005].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As mentioned previously, although diagnostic biopsy has significant predictive value, the chance that sperm cannot be retrieved on the day of oocyte retrieval is 25% -30% [Glina et al 2005]. Some have suggested that the cryopreservation of sperm from TESE before treatment should be implemented to prevent this situation [Wu et al 2005].…”
Section: Discussionmentioning
confidence: 99%
“…However, spermatogenesis in NOA is usually limited, with only small foci spread over limited areas, so retrieving sperm can be a challenge. Diagnostic biopsy has significant predictive value, but the chance that no sperm will be found is 25%-30% [Glina et al 2005]. If sperm are not obtained then cryopreservation of oocytes or use of a sperm donor is the only possible alternative.…”
Section: Introductionmentioning
confidence: 99%
“…More advanced histopathological results, such as MA and hypospermatogenesis, have correlated with the detection of spermatozoa during initial and repeat TESE. 23,24 Favorable testicular histopathology, such as late MA and hypospermatogenesis, may also influence the therapeutic effects of clomiphene citrate 15 and varicocele repair. 25 …”
Section: Discussionmentioning
confidence: 99%
“…However, its use is limited, as the patient must undergo a prognostic biopsy, which adds a surgical procedure. The worst pattern for sperm recovery is Sertoly cell-only syndrome, which has a rate of sperm retrieval ranging from 4-51%; maturation arrest (8-80%) is affects sperm recovery adversely, while hypospermatogenesis produces high rates of sperm recovery (80-100%) (3,28,29). …”
Section: Histologic Patternmentioning
confidence: 99%
“…Prognostic factors have included testis size, follicle stimulating hormone (FSH), inhibin beta, the etiology of infertility, and genetic alterations; however, the histological testicular pattern remains the best predictor of sperm retrieval, although with the inconvenience of a second invasive procedure (3). …”
Section: Introductionmentioning
confidence: 99%